Characterization of Treponema pallidum Dissemination in C57BL/6 Mice - Lu, Simin; Zheng, Kang; Wang, Jianye; Xu, Man; Xie, Yafeng; Yuan, Shuai; Wang, Chuan; Wu, Yimou (Frontiers in Immunology, 2021)
The spirochetal pathogen Treponema pallidum causes 5 million new cases of venereal syphilis worldwide each year. One major obstacle to syphilis prevention and treatment is the lack of suitable experimental animal models to study its pathogenesis. Accordingly, in this study, we further evaluated the responses of mice to Treponema pallidum. Reverse transcription polymerase chain reaction showed that Treponema pallidum could colonize the heart, liver, spleen, kidneys, and testicles of C57BL/6 mice, and the organism rapidly penetrated the blood-brain barrier in mice by 24 h after infection. In subsequent rabbit infectivity tests, we observed evident signs of the microorganism in the testicular interstitium. After infection, bacterial loads were higher in the tissues than in the blood of C57BL/6 mice. Moreover, a significant Th1 immune response was recorded by cytokine assays. Flow cytometric analysis suggested an obvious increase in the proportion of CD3+T and CD4+ T cells in the spleen cells in the infected mice. Thus, improving our understanding of the response of C57BL/6 mice for Treponema pallidum will help to comprehensive elucidate the pathogenic mechanisms of this bacterium and and lay the foundation for the development of a new research model of Treponema pallidum.